Analysis of a wood production strategy from expert perspectives - Claudie-Maude Canuel; Anne Bernard; Nelson Thiffault; Nancy Gélinas; Pierre Drapeau; Evelyne Thiffault; Nicolas Bélanger (The Forestry Chronicle)
In 2020, Quebec adopted a strategy to increase the quantity and quality of timber it produces. During a roundtable discussion held in the fall of 2021, experts in forestry and in related fields expressed their views on the new strategy and its implementation challenges. The main purpose of this article is to present the key observations from the roundtable. The observations addressed two themes: the general context in which the strategy was developed, and the context of its implementation on the ground. Although most of the panellists agreed on the relevance of such a strategy, particularly as regards to climate change mitigation and wealth creation, several questions remain. The challenge of harmonizing uses, regionalization, spatialization of management decisions, labour shortage, and uncertain ecosystem dynamics make it difficult to assess the strategy’s potential impact on the ground and its ability to achieve its targets.